Antibiotic Dosing in Critically Ill Patients Receiving CRRT: Underdosing is Overprevalent. Issue 5 (September 2014) - Lewis, Susan J.; Mueller, Bruce A.
Abstract Published CRRT drug dosing algorithms and other dosing guidelines appear to result in underdosed antibiotics, leading to failure to attain pharmacodynamic targets. High mortality rates persist with inadequate antibiotic therapy as the most important risk factor for death. Reasons for unintended antibiotic underdosing in patients receiving CRRT are many. Underdosing may result from lack of the recognition that better hepatic function in AKI patients yields higher nonrenal antibiotic clearance compared to ESRD patients. Other factors include the variability in body size and fluid composition of patients, the serious consequence of delayed achievement of antibiotic pharmacodynamic targets in septic patients, potential subtherapeutic antibiotic concentrations at the infection site, and the influence of RRT intensity on antibiotic concentrations. Too often, clinicians weigh the benefits of overcautious antibiotic dosing to avoid antibiotic toxicity too heavily against the benefits of rapid attainment of therapeutic antibiotic concentrations in critically ill patients receiving CRRT. We urge clinicians to prescribe antibiotics aggressively for these vulnerable patients.